Automated And Reliable Smart Home System Using Blockchain - Macharla Umamaheswara Rao, Amarendra Jadda (International Journal of Advanced Science and Technology, 2020)
Emergency service call for public service providers has become an important role for smart home applications in order to support safety and security in the household building. Blockchain has been a promising solution with cryptography and incentive distributed mechanisms to support the verification, execution and recording of transactions between untrusted parties. These objects are often deployed in open environments to provide innovative services in various application domains such as smart cities, smart health, and smart communities. IoT devices produce a massive amount of confidentiality and security-sensitive data. Thus, security of these devices is very important in order to ensure the safety and effectiveness of the system. This project presents emergency service for a Smart Home System (SHS) based on Ethereum blockchain with smart contract for decentralized handling access control among untrusted public services so called Home Service Providers (HSPs) and smart home IoT devices.